Dragon in the Tropics : Venezuela and the Legacy of Hugo Chavez - Corrales, Javier, 1966-; Penfold-Becerra, Michael (Brookings Latin America Initiative book., 2015)
"A study of the Venezuelan revolution headed by Hugo Chávez, first elected president in 1999, with emphasis on how Chávez took a frail but still pluralistic democracy and turned it into a semi-authoritarian regime, achieving political transformation at great cost to the country's institutions, including its oil industry"--Provided by publisher.